Titanium Dioxide Promotes the Growth and Aggregation of Calcium Phosphate and Monosodium Urate Mixed Crystals - Onyebuchi C. Ukaeje; Bidhan C. Bandyopadhyay (Crystals, 2023)
The increased utilization of titanium dioxide (TiO2) nanoparticles (TNPs) in various industrial and consumer products has raised concerns regarding its harmful effect due to its accumulation within the different systems of the human body. Here, we focused on the influence of TNPs on the growth and aggregation of two crucial crystalline substances, calcium phosphate (CaP) and monosodium urate (MSU), particularly its implications in gout disease. In this study, we adopted microscopic techniques and generated kinetic models to examine the interactions between TNPs, CaP and MSU, and crystallization, under controlled laboratory conditions. Our findings reveal that TNPs not only facilitate the growth of these crystals but also promote their co-aggregations. Crystal dissolution kinetics also exhibit that an increase in TNPs concentration corresponds to a reduction in the dissolution rate of CaP and MSU crystals in presence of the dissoluting agent hydroxycitrate (Hcit). These observations suggest that TNPs can stabilize CaP+MSU mixed crystals, which underscores the significance of TNPs’ exposure in the pathogenesis of gout disease.